2019
DOI: 10.1101/660779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning reveals bilateral distribution of somatic L1 insertions in human neurons and glia

Abstract: Active retrotransposons in the human genome (L1, Alu and SVA elements) can create genomic mobile element insertions (MEIs) in both germline and somatic tissue 1 . Specific somatic MEIs have been detected at high levels in human cancers 2 , and at lower to medium levels in human brains 3 . Dysregulation of somatic retrotransposition in the human brain has been hypothesized to contribute to neuropsychiatric diseases 4,5 . However, individual somatic MEIs are present in small proportions of cells at a given anato… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…We chose not to analyze rare mobile element insertions because variant calling for these variants appear to be noisy from our 30× WGS and there was a lack of external dataset or analytic approach for the need of quality control. Increased somatic L1 insertions have been recently reported in neurons of schizophrenia patients using postmortem brain tissues 45 . The detection of somatic L1 insertions required very deep WGS (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose not to analyze rare mobile element insertions because variant calling for these variants appear to be noisy from our 30× WGS and there was a lack of external dataset or analytic approach for the need of quality control. Increased somatic L1 insertions have been recently reported in neurons of schizophrenia patients using postmortem brain tissues 45 . The detection of somatic L1 insertions required very deep WGS (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…200×) and tailored analytic methods (e.g. machine learning 45 ). For similar reasons, we also chose not to evaluate translocations and complex SVs in this study as we feel that these variants can be better detected from WGS using long-insert jumping libraries, deeper coverage, and targeted capture of breakpoints 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that a recurrent intronic deletion results in the exonization of an Alu element that is found in 6% of families with mild hemophilia A in France 13 . Somatic L1 retrotransposition can occur in neuronal progenitor cells [14][15][16][17][18] , indicating a possible role for L1s in the etiology of neuropsychiatric diseases 19 . In addition, a mutagenic L1 insertion that disrupted the 16th exon of the APC gene has been shown to instigate colorectal tumor development 9 .…”
mentioning
confidence: 99%
“…As an alternative to single‐cell sequencing with its high experimental costs and amplification bias, some recent studies have used a bulk sequencing approach with high sequencing coverage to detect low‐level mosaic somatic insertions in the brain and other tissues. RetroSom is a machine learning−based tool that detects somatic L1 and Alu insertions from ultra‐high‐depth WGS, and its application to ∼200× bulk WGS of sorted neurons and glia revealed two brain‐specific somatic L1 insertions at ∼1% mosaicism (Zhu et al., 2019). Furthermore, HAT‐seq, a PCR‐based targeted bulk sequencing approach, identified somatic L1 insertions with low‑level mosaicism in neurons and non‐brain tissues (Zhao et al., 2019).…”
Section: Identification Of Different Types Of Te Insertionsmentioning
confidence: 99%